Дослідження загальних тенденцій сучасного розвитку виробництва аміаку - Бабіченко, Анатолій Костянтинович; Азаров, Микола Іванович; Бабіченко, Юлія Анатоліївна; Красніков, Ігор Леонідович; Лисаченко, Ігор Григорович (Полтавська державна аграрна академія, ПП "Технологічний Центр", 2014)
У статті розглянуто основні етапи еволюції виробництва синтетичного аміаку. У контексті цих етапів проаналізовані та встановлено загальні тенденції сучасного розвитку, зокрема для України, аміачного виробництва. Обґрунтовано, що природний газ в найближчі десятиріччя як і раніше буде основною сировиною в технології аміачного виробництва. При цьому особливо актуальною для вітчизняних агрегатів залишається тенденція підвищення їх енергоефективності.

The evolution stages of synthetic ammonia production were considered in the paper. In the context of these stages, according to the results of analytical studies, general development trends of ammonia production in the present conditions, in particular for Ukraine, which cover both problems and individual tasks, required for overcoming and solving them were analyzed and determined. It was shown that the need to solve food program is associated with the trend of ever-increasing nitrogen fertilizers production volume, both in the world and in Ukraine, which is accompanied by a corresponding increase in the ammonia production volume. It was proved that, in the coming decades, the natural gas will continue to be the main raw material in the ammonia production technology. Herewith, a tendency to increase their energy efficiency by upgrading instrumentaltechnological design of the most energy intensive stages, in particular ammonia condensation, in order to reduce electricity and natural gas consumption rates, which can be achieved by utilizing low-grade heat of flows with the temperature less than 100 °C is especially relevant for domestic units. The latter can be achieved by using steam-ejector refrigeration systems.
Study of general trends of modern development of ammonia production
Keywords: виробництво аміаку; хімічна промисловість; аміачне виробництво; азотні добрива; ammonia production